Culture & empire : digital revolution - Hintjens, Pieter, ....- (S.l. : iMatix Global Services, 2013)
The whole planet is getting connected and building vast new communities. Billions of us are online, all the time. This online world thinks faster, and thinks differently. Smart, fast, and creative, our new communities are a very real challenge to old power and old money. And old money -- after its War on Drugs and War on Terror -- is now launching its War on the Internet. What is going on, and where will this lead us? Pieter Hintjens -- author, programmer, and activist -- tells all in this vast story of Culture & Empire: Digital Revolution.